Anti-Inflammatory Potential of Carpomitra costata Ethanolic Extracts via Inhibition of NF-κB and AP-1 Activation in LPS-Stimulated RAW264.7 Macrophages. (26th February 2018) - Yim, Mi-Jin; Lee, Jeong Min; Choi, Grace; Lee, Dae-Sung; Park, Won Sun; Jung, Won-Kyo; Park, Saegwang; Seo, Su-Kil; Park, Jungik; Choi, Il-Whan; Ma, Sun Young
Abstract : Marine algae have valuable health and dietary benefits. The present study aimed to investigate whether an ethanol extract of Carpomitra costata (CCE) could inhibit the inflammatory response to LPS. CCE attenuated the production of proinflammatory mediators, such as prostaglandin E2 (PGE2 ) and nitric oxide (NO), by inhibiting inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) expression in LPS-induced RAW264.7 macrophages. CCE also inhibited the expression of proinflammatory cytokines such as IL-1 β, TNF- α, and IL-6. CCE suppressed the LPS-induced DNA-binding activity of (NF- κ B) and activator protein-1 (AP-1). In addition, CCE attenuated the LPS-stimulated phosphorylation of c-Jun N-terminal kinase/stress-activated protein kinase (JNK) and phosphatidylinositol 3′-kinase/Akt (PI3K/Akt). Functional aspects of the JNK and Akt signaling pathways were analyzed using specific inhibitors, which attenuated the LPS-induced production of proinflammatory cytokines, and NO and PGE2 expression by suppressing AP-1 and NF- κ B activity. In particular, the AP-1 signaling pathway is not involved in the production of inflammatory cytokines, such as IL-6, TNF- α, and IL-1 β . These results suggested that CCE might exert its anti-inflammatory action by downregulating transcriptional factors (NF- κ B and AP-1) through JNK and Akt signaling pathways. The current study suggested that CCE might be a valuable candidate for the treatment of inflammatory disorders.